Damage Identification of Rotating Blades Based on Fuzzy C-Means and Frequency Response Function Curvature Methods - Ruize Cui; Zefeng Wang; Zhiguang Song (International Journal of Aerospace Engineering)
Rotor blades are one of the key components of helicopter. If the blades are damaged, the safety and reliability of the helicopter will be seriously affected. Therefore, it is necessary to investigate the damage identification of the rotating blades. In this paper, a rotating cantilever beam is used to model the rotor blade. Based on the assumed mode method and Hamilton’s principle, the equation of motion is formulated, and the correctness of the model is verified by numerical and experimental studies. Altogether, two methods are used to identify the damages on the blade. The first one is the cluster analysis method based on the fuzzy C-mean theory. In order to reduce the dimension of the signal features, the singular value decomposition is introduced. The second method is the curvature of frequency response function method that can be used to determine the exact position of damages. Simulation results show that one can use fuzzy C-mean method to determine whether there is damage on the blade firstly and then determine the exact position of the damage through the curvature of frequency response function method.